NUMERICAL SOLUTION OF THE SECOND BOUNDARY VALUE PROBLEM FOR AN EQUATION OF MIXED-COMPOSITE TYPE - Berdiyevna, Merajova Shahlo (Journal of Global Research in Mathematical Archives(JGRMA), 2019)
We consider difference scheme for the second boundary-value problem for a general mixed-type equation in a space Rn+1 , which degenerates inside and also at the boundary of the domain of definition. For the numerical solution of the problem we offer the stably difference scheme.Â  Here, using some examples, we show the unique solvability of the difference scheme and present the results of a numerical calculation. For this, we use a mathematical package - the Mathcad program.